2015
DOI: 10.1007/s00268-015-3144-z
|View full text |Cite
|
Sign up to set email alerts
|

Staging Laparoscopy for Patients with cM0, Type 4, and Large Type 3 Gastric Cancer

Abstract: SL is useful for detecting previously unsuspected peritoneal metastasis and for avoiding unnecessary laparotomy, although the high false-negative rate cannot be ignored. Patients with cM0, type 4, and large type 3 gastric cancer are considered suitable candidates for SL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 29 publications
2
36
0
1
Order By: Relevance
“…The main purpose of SL was to find disseminated nodules that could not be detected by imaging, but other clinical findings that could change the therapeutic strategy (such as liver metastases or invasion to adjacent organs) may be detected at SL. Irino et al, Hosogi et al, Miki et al, Ishigami et al, Yamagata et al and Nakagawa et al reported the detection rate of P1 and/or CY1 as 47%, 45%, 53.4%, 42.7%, 46% and 51.6%, respectively. Results of these studies from Japanese institutions were almost similar (range: 42.7% to 53.4%), and higher than those from other countries (range: 7.8% to 40%) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main purpose of SL was to find disseminated nodules that could not be detected by imaging, but other clinical findings that could change the therapeutic strategy (such as liver metastases or invasion to adjacent organs) may be detected at SL. Irino et al, Hosogi et al, Miki et al, Ishigami et al, Yamagata et al and Nakagawa et al reported the detection rate of P1 and/or CY1 as 47%, 45%, 53.4%, 42.7%, 46% and 51.6%, respectively. Results of these studies from Japanese institutions were almost similar (range: 42.7% to 53.4%), and higher than those from other countries (range: 7.8% to 40%) .…”
Section: Resultsmentioning
confidence: 99%
“…We also questioned whether the total length of mesentery must be inspected. Ishigami et al and Miki et al included “the surface of the entire bowel” and “from the oral to anal side “in the exploration area of SL, but there was no description in other reports. Definite answers could not be drawn from the reported articles, but wide exploration may be needed to reduce false‐negative results.…”
Section: Resultsmentioning
confidence: 99%
“…Second, preoperative staging without staging laparoscopy could have resulted in over-staging, particularly in cases of peritoneal seeding. Diagnostic staging laparoscopy and re-evaluation of peritoneal metastasis with staging laparoscopy might be helpful in improving the diagnostic accuracy and optimizing candidates for conversion surgery [26,27]. Third, the clinical efficacy of cancer dormancy marker expression in conversion surgery cannot be definitively concluded, given the relatively small sample size of this study.…”
Section: Discussionmentioning
confidence: 92%
“…Identifying patients at higher risk of nonperitoneal recurrence after curative gastrectomy could provide survival benefit to patients by offering more intensive postoperative follow-up, on the basis of our present findings. It is well known that undifferentiated-type and serosa-invasive adenocarcinoma is frequently associated with peritoneal recurrence [24], whereas differentiated-type adenocarcinoma is related to nonperitoneal recurrence [25]. If we can predict a similar recurrence pattern with high accuracy, we could offer the most suitable follow-up schedule to each patient accordingly.…”
Section: Discussionmentioning
confidence: 99%